(X+15)(x-12)=0

Simple and best practice solution for (X+15)(x-12)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (X+15)(x-12)=0 equation:


Simplifying
(X + 15)(x + -12) = 0

Reorder the terms:
(15 + X)(x + -12) = 0

Reorder the terms:
(15 + X)(-12 + x) = 0

Multiply (15 + X) * (-12 + x)
(15(-12 + x) + X(-12 + x)) = 0
((-12 * 15 + x * 15) + X(-12 + x)) = 0
((-180 + 15x) + X(-12 + x)) = 0
(-180 + 15x + (-12 * X + x * X)) = 0
(-180 + 15x + (-12X + xX)) = 0

Reorder the terms:
(-180 + -12X + 15x + xX) = 0
(-180 + -12X + 15x + xX) = 0

Solving
-180 + -12X + 15x + xX = 0

Solving for variable 'X'.

Move all terms containing X to the left, all other terms to the right.

Add '180' to each side of the equation.
-180 + -12X + 15x + 180 + xX = 0 + 180

Reorder the terms:
-180 + 180 + -12X + 15x + xX = 0 + 180

Combine like terms: -180 + 180 = 0
0 + -12X + 15x + xX = 0 + 180
-12X + 15x + xX = 0 + 180

Combine like terms: 0 + 180 = 180
-12X + 15x + xX = 180

Add '-15x' to each side of the equation.
-12X + 15x + -15x + xX = 180 + -15x

Combine like terms: 15x + -15x = 0
-12X + 0 + xX = 180 + -15x
-12X + xX = 180 + -15x

Reorder the terms:
-180 + -12X + 15x + xX = 180 + -15x + -180 + 15x

Reorder the terms:
-180 + -12X + 15x + xX = 180 + -180 + -15x + 15x

Combine like terms: 180 + -180 = 0
-180 + -12X + 15x + xX = 0 + -15x + 15x
-180 + -12X + 15x + xX = -15x + 15x

Combine like terms: -15x + 15x = 0
-180 + -12X + 15x + xX = 0

The solution to this equation could not be determined.

See similar equations:

| (-p)-(-4)(-2-p)=-(4-2p) | | 0.07x+0.09(20000-x)= | | -10=-14t+14t | | 0.07x+0.09(20000-x)=1550 | | 5x-6=2x+15 | | 4x^2-100=25 | | 7-3[4-(3y-9)]= | | 0.97n+5.9=11.77 | | 4(b-5)-3b=-33+12 | | 8d+7=5d+58 | | 4x^2+400=25 | | x(19-2x)(35-2x)=0 | | 52/9+23/15 | | X-7=3y-4 | | 7=-13-d | | 6/377+8/15+4/9 | | 8h-3=2h+1forh | | 9x-3x=7(x-3)+8 | | 8h=2h+24 | | H=-16t^2+784 | | -20x^2+20x+75= | | 11.2/-1.6 | | 13-5x=3x+11 | | 182/14 | | 14/182 | | 6x*x-10x+10=0 | | 5(t-2)=25 | | 2d*d-10d-9=0 | | 7p-(3p+14)=18 | | 3n*n-7n-8=0 | | 9+12x=29+8x | | 3*150-4=90 |

Equations solver categories